MENAKAR KEMUNGKINAN DEMOKRASI YANG ISLAMIK - Windy Dermawan; RMT Nurhasan Affandi; Gilang Nur Alam (UNIDA Gontor, 2019)
This research aims to find the possible compatibility between Islam and democracy which has always been a polemic in the Muslim world. To achieve this, researchers explore the debate about Islam and democracy among the academics and Islamists. This research uses qualitative methods by collecting data through interviews with a number of informants and documentation studies. The findings of this research conclude that the concept of Islamic democracy can be a bridge to the debate about Islamic compatibility with democracy. Some derivations that cover this concept are shura (consultation), ijma '(consensus), bai'at (pledge of allegiance), and ijtihad (interpretive justification). Islamic democracy with some of its derivatives do not necessarily represent Islam but reflects particular Islamic options. Therefore, the compatibility of Islam and democracy through the concept of Islamic democracy is not comprehensively Islamic but Islamic and not comprehensively democratic but is democratic. This concept plays as the distinctive character for Muslim society when they develop democracy.